Implementation Plan and Solutions to the Challenges Faced by Medical Faculty During COVID-19 Pandemic: Transition to the New Normal - Ammara Hameed; Shazia Fakhir; Shakeel Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess faculty perception regarding the transition from traditional to online classrooms and highlight the problems and devise possible solutions for these problems.